PENGARUH BOARDING SCHOOL TERHADAP DISIPLIN, MOTIVASI, DAN MINAT BELAJAR SISWA PADA MATA PELAJARAN KEWIRAUSAHAAN KELAS X SMKN PERTANIAN TERPADU PROVINSI RIAU: (The Effect on Boarding School Discipline, Motivation and Interest on Student Learning Subject of Entrepreneurship Class X SMKN Pertanian Terpadu Provinsi Riau) - Tity Hastuti; Jumidah Jumidah (UIR Press, 2016)
This study aims to determine the effect of the boarding school discipline, motivation, andinterest in learning students at SMK Integrated Agricultural Riau Province. This research wasconducted in February 2016. The subjects were students of class X in SMK IntegratedAgricultural Riau Province. The research sample consisted of 186 students in 94 studentdormitories, students outside the dormitory 92 students. Collecting data in this study by using aquestionnaire (questionnaire) to collect data on the influence of boarding school discipline,motivation, and student interest in entrepreneurship subjects in the Provincial IntegratedAgricultural SMKN Riau.Analisis used in this study is the normality test, homogeneity and testsamples t-test. The results of this study conducted by statistical calculation that students learnthe discipline of 2.139 with the high category, for the motivation to learn at 3.292 categorized asvery high, and interest in learning amounted to 2.513 with the high category. From the results ofthis study concluded that there are significant boarding school to discipline, motivation, andstudent interest in entrepreneurship subjects at SMK Integrated Agricultural Riau Province